Improving Knowledge of Clean and Healthy Behavior in Students at SMP Muhammadiyah 2 Bolang - Ariawan, Fajriah; Afiah, Gina; Arifin, Heru Bustanul; Junianti, Inggit; Hilman, Mayliany; arumsari, cucu (AbdimasMu UMTAS, 2023)
PHBS stands for Clean and Healthy Lifestyle. While the notion of PHBS is all health behaviors that are carried out because of the personal awareness of the family and all its members are able to help themselves in the health sector and have an active role in community activities. . The counseling material delivered was about PHBS and how to wash hands for junior high school students. This activity was carried out at SMP 2 Bolang using lecture, discussion and simulation methods. The result of this activity is that students understand about clean and healthy living behavior (PHBS) and how to wash hands properly and correctly, where students are able to the answers given after health counseling and being able to re-practice independently how to wash hands properly and correctly. In addition, students participated in the activity enthusiastically so that it became the beginning to improve patterns and lifestyles to make them healthier